Towards circular cities – exploring the circular economy approach in context of municipal solid waste - Rivera, Alejandro Guzmán; Jarzębowski, Sebastian; Romero León, Katia; Bourlakis, Michael (Polskie Wydawnictwo Ekonomiczne S.A., 2023)
The objective of this research is to determine whether the city under investigation in a developing country is pursuing a "circular city" model based on various indicators and the city's current characteristics. The city under analysis was Xalapa, the capital city of the state of Veracruz in Mexico. To accomplish our research goals, we employed a qualitative methodology. We conducted interviews with the government representative responsible for municipal solid waste management during the designated period, as well as with the proprietors of the 18 most prominent private waste collection centers. Additionally, we obtained relevant information from the government through the transparency platform. For our assessment, we used the waste-focused indicators provided by L. Girard and F. Nocca. Our analysis indicates that the city under investigation is not on the trajectory towards adopting a "circular city" model. However, the context of municipal solid waste (MSW) offers valuable suggestions for future implementation of circular economy (CE) practices. The findings presented in this study offer valuable insights for researchers in other developing countries who are also engaged in exploring the issues discussed. Also, the lessons derived from this study hold relevance for cities in developing countries, as they grapple with environmental and economic degradation similar to the city studied.
Keywords: circular economy; municipal solid waste; waste management